Influence of Moringa Oleifera Leaf Meal Used as Phytogenic Feed Additive on the Serum Metabolites and Egg Bioactive Compounds in Commercial Layers - Ahmad,S (2018)
ABSTRACT Phytogenic feed additives have been increasingly used in the last decade, and several plants and their metabolites have been investigated for the said purpose. In this context, present study aimed at evaluating the effects of Moringa oleifera as feed additive on layer performance, and egg bioactive compound levels and nutrient profile. HyLine W36 layers (n=200), 50 weeks of age, were randomly distributed in four treatments with five replicates of ten birds each. Four isocaloric (2725 kcal/kg) and isonitrogenous (CP 16%) diets were formulated and supplemented with 0, 0.5, 1.0, or 1.5% (w/w) of dried Moringa oleifera leaf powder (MLM). The results showed positive effects of MLM on egg production, egg mass, and feed conversion ratio, but negative effects on egg quality (p≤0.05). The contents of bioactive compounds, like β-carotene, quercetin, and selenium, in the diet and in the egg yolk were significantly (p≤0.05) higher in the group fed1.5% MLM, with values of 8.90, 48.88, and 0.54 mg/kg feed and 4906, 241 and 56.82 µg/100g yolk, respectively. Creatinine and glucose serum levels and cholesterol levels (serum and eggs) linearly increased as a function of increasing MLM dietary levels (p≤0.05). Antibody titers against Newcastle Disease significantly improved (p≤0.05) in the group fed the diet supplemented with 1.5% MLM. It was concluded that Moringa oleifera used as phytogenic feed additive enriches eggs with bioactive and functional compounds, and improves the production performance and the health status of layers.